A switchable NO-releasing nanomedicine for enhanced cancer therapy and inhibition of metastasis. Issue 12 (11th March 2019) - Xu, Yan; Ren, Hao; Liu, Jiwei; Wang, Yonglu; Meng, Zhengjie; He, Zhanjie; Miao, Wenjun; Chen, Guoguang; Li, Xueming
Abstract : Clinical chemotherapy for cancer is limited by the physiological barrier of tumors, resulting in low drug delivery to tumors, poor efficacy of drugs and inability to block tumor metastasis. Abstract : Clinical chemotherapy for cancer is limited by the physiological barrier of tumors, resulting in low drug delivery to tumors, poor efficacy of drugs and inability to block tumor metastasis. Here we developed an intelligent switchable nitric oxide (NO)-releasing nanoparticle, IPH-NO, which loads a photosensitizer (IR780) and the chemotherapy drug paclitaxel (PTX) into NO donor-S-nitrosated human serum albumin (HSA-NO). NO exhibits two effects based on its concentration: enhancement of chemotherapy by increasing the enhanced permeability and retention (EPR) effect at low concentrations and direct killing of cancer cells at high concentrations. IPH-NO can slowly release NO in the presence of glutathione to boost tumor vascular permeability and improve drug accumulation. Near-infrared light irradiation was utilized to induce a quick release of NO that can directly kill cancer cells at high concentrations. This combination of phototherapy and NO gas therapy activated by NIR together with chemotherapy showed significant effects in tumor inhibition. Furthermore, IPH-NO blocked tumor metastasis by inhibiting epithelial mesenchymal transition. PH-NO provides a novel strategy to control NO release at tumor site for drug accumulation and combination therapies, consequently potentiating the anticancer efficacy and inhibiting tumor metastasis.